Governance of complex systems: a multi-level model - Weyer, Johannes; Adelt, Fabian; Hoffmann, Sebastian (Technische Universität Dortmund, 2015)
Social and political sciences have discussed the issue of governance of complex systems for a long time, but still lack consensus on terms, mechanisms and the performance of different modes of governance. The paper at hand adopts an analytical perspective of governance and develops a general framework of it, rooted in a sociological macro-micro-macro model. It defines the basic mechanisms “control” and “coordination” and depicts “governance” as a specific combination of these basic mechanisms in multi-level socio-technical systems. We claim that successful governance has to solve several problems simultaneously: the governance of singular levels within a multi-level architecture as well as the interplay between them. The heuristic value of this framework will be demonstrated by the sample of modern infrastructure systems (e.g. aviation or energy grids). Here we typically observe a combination of three distinct levels: the coordination in negotiation processes, the regulation of functional subsystems of society, and the operational control of these systems.
Soziologische Arbeitspapiere;42/2015
Keywords: governance; multi-level model; complexity; coordination; control; 300; 330